Vesicles as a Tool for Enhanced Topical Drug Delivery - Nandgude, Tanaji D. (Asian Journal of Pharmaceutics (AJP), 2016)
Designing of a drug in the vesicular system has brought a new life to the old pre-existing drug and thus has improved its therapeutic efficacy by controlling and sustaining the actions. As skin is one of the crucial and important organs of the human body, delivering the drug across it requires an effective development in the field of research. Topical drug delivery system is specifically designed with the objective to accomplish the delivery of therapeutically active drugs across the skin. Vesicular carriers are one of the recently invented carriers. Liposomes, niosomes, transfersomes, and ethosomes constitute the major part of these vesicles that have been sufficiently employed for the treatment of variety of topical skin diseases. In the past few years, various research reports on the development of topical carrier systems showed that these carriers have emerged as a novel vesicular carrier. The present review focuses on the topical delivery via these vesicles, emphasizing on various aspects of all these carriers.